“Good Day! My name is Martin and I am Danish citizen”: problem-solving, knowledge-sharing, and trust in online interaction ‒ the case of family reunification - Jensen, Astrid; Grindsted, Annette (MedieKultur: Journal of media and communication research, 2012)
This article focuses on opportunities for citizens to interact with public organisations in the processing of individual cases and how this interaction is facilitated by the Internet. We analysed a string of messages from the online forum of the non-governmental organisation Marriage without Borders, which offers dialogue-based advice to members looking for help prior with the complex application process in relation to family reunification visas in Denmark. The trajectory of the problem-solving interaction clearly demonstrates the Internet’s potential for dynamic online interaction, emphasising the timeliness of a joint accomplishment. Our findings also emphasise the potential of non-governmental web forums to address the needs of member publics and to serve as equalisers in relation to the power gap between the more powerful public authorities and the less powerful individuals. A recurrent theme running through these posts is that you trust the members of the community to help as best they can and that expertise is not allocated to the authorities alone.